Synthesis of a Tethered myo-Inositol (1,3,4,5,6)Pentakisphosphate (IP5) Derivative as a Probe for Biological Studies - Gregory, Mark; Catimel, Bruno; Yin, Meng-Xin; Condron, Melanie; Burgess, Antony W.; Holmes, Andrew B. (Synlett, 2016)
There is sufficient evidence to suggest that myo-inositol pentakisphosphate is a vital intermediate species in higher inositol phosphate metabolism, however, its biological roles and physiological function in cells remain uncertain. A tethered myo-inositol pentakisphosphate (IP5) derivative with a terminal amine group is synthesised allowing facilitated immobilisation onto M-270 magnetic Dynabeads for pull-down experiments and biosensor chip preparation for surface plasmon resonance studies. The probes are validated by both pull-down and surface plasmon resonance (SPR) studies of the known binding protein GRP-1 (general receptor for phosphoinositides 1), and furthermore by SPR studies of protein kinase B (PKB or AKT) binding.
Keywords: protecting groups; proteins; total synthesis; regioselectivity; carbohydrates; phosphates; bioorganic chemistry; hydrogenation